Current state of the foreign trade of the Republic of Moldova with agri-food products - Stratan, Alexandru; Lucasenco, Eugenia (<center>Conference Proceedings Determinants Of Regional Development</center>, 2022)
The paper aims to discuss the latest developments in the foreign trade with agri-food products of the Republic of Moldova, as it represents an important pillar for the general trade in goods. Agri-food exports have a constant high share in the total trade of over 40%, thus confirming the high importance of the sector for the national economy. The trade values of the commodity groups 1-24 have been analyzed, also pointing to the most competitive groups of products on the international market by using the Revealed Comparative Advantage indicator. A quantitative and qualitative analysis has been performed while observing the trade data at the level of imports and exports for the period 2010 – 2021. As a result, a series of recommendations have been provided in order to increase the competitiveness of Moldovan agri-food products, like enhancing investments in added value sub-sectors, improvement of the quality of products, investments in post-harvest and processing infrastructure, etc.